Traumatic Brain Injury (TBI) in School-Based Populations: Common Sequelae and Assistive Technology Interventions - Martinez, Amy Pacos; Scherer, Marcia J.; Tozser, Timea (Advances in neurodevelopmental disorders, 2018)
Traumatic brain injury is the leading source of injury and death among children within the USA and worldwide. According to the World Health Organization, traumatic brain injury will surpass many diseases as the primary cause of death and disability in children within the next few years. A traumatic brain injury is the result of an outside force striking the head in any manner causing the brain to become structurally damaged. Dependent on the severity of the injury, there are persistent lifelong deficits a child may endure. The present article reviews the symptomology of children who sustain a traumatic brain injury and demonstrates the significant impact on future academic achievement. Thus, emphasizing the value of neuropsychological evaluations in aiding children, parents, providers, and educators to select tools such as assistive technology to help children achieve developmental milestones, perform at appropriate age levels in academic contexts, and build compensatory strategies. The vast array of AT options can provide much-needed support to children with varying cognitive needs. Further, the implementation of assistive technology for children is critical in breaking down barriers in academia and allowing for additional research in the field of assistive technology.